1998
DOI: 10.1111/j.1540-8159.1998.tb00211.x
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Adaptation of the Basic Pacing Rate in Response to Minute Ventilation

Abstract: Rate responsive pacing based on minute ventilation (VE) correlates highly with metabolic demand. This type of sensing also recognizes extended periods of rest. The Chorum pacemaker includes a rate responsive algorithm that modulates the basic rate according to phases of activity versus sleep. Forty-six patients (mean age 78 +/- 15), received a Chorum pacemaker for atrioventricular block in 17 cases, sick sinus syndrome in 25, and mixed disorders in 4. Holter monitoring was performed to analyze to heart rate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The prevalence of obstructive sleep apnea may be at least 30% in patients with permanent pacemakers (PMs), 8 and that of SAS may be even higher among patients who also have congestive heart failure. Some rate‐response PMs use measurement of transthoracic impedance to provide an index of minute ventilation (MV) as a modality for rate response in patients with chronotropic incompetence 9 . Acute studies have shown a high correlation between estimated MV and oxygen consumption during exercise tests 10,11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of obstructive sleep apnea may be at least 30% in patients with permanent pacemakers (PMs), 8 and that of SAS may be even higher among patients who also have congestive heart failure. Some rate‐response PMs use measurement of transthoracic impedance to provide an index of minute ventilation (MV) as a modality for rate response in patients with chronotropic incompetence 9 . Acute studies have shown a high correlation between estimated MV and oxygen consumption during exercise tests 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Some rate-response PMs use measurement of transthoracic impedance to provide an index of minute ventilation (MV) as a modality for rate response in patients with chronotropic incompetence. 9 Acute studies have shown a high correlation between estimated MV and oxygen consumption during exercise tests. 10,11 However, transthoracic impedance measurements also can be optimized to track each respiratory cycle and provide estimates of variation in tidal volume.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Minute ventilation sensors were also used to modulate the basic pacing rate during extended resting periods. [9][10][11] Such a sensor-based approach carries theoretical advantages, especially in individuals who take frequent naps and those who arise in the middle of the night for a trip to the bathroom. This type of a dynamic sleep mode was introduced in Pacesetter Trilogy pacemakers (St. Jude Medical CRMD, Sylmar, CA, USA).…”
mentioning
confidence: 99%